The complement component 1 q (C1q) in Nile tilapia (Oreochromis niloticus): Functional characterization in host defense against bacterial infection and effect on cytokine response in macrophages. (October 2018) - Chen, Meng; Ding, Mingmei; Li, Yuan; Zhong, Xiaofang; Liu, Shuo; Guo, Zheng; Yin, Xiaoxue; Fu, Shengli; Ye, Jianmin
Abstract: Complement component 1q (C1q) is the initial protein of the classical complement pathway and plays an important role in immune response against bacterial infection. In this study, the full-length of C1q subcomponent A, B and C chain genes ( C1qA, C1qB and C1qC ) were identified and characterized from Nile tilapia ( Oreochromis niloticus ). Molecular characterization of these three C1q subcomponents ( OnC1qs ) harbored conserved amino acids through analyses of multiple sequence alignment and phylogenetic tree, which were homologous to other teleost species. Expression analysis revealed that the OnC1qs were highly expressed in liver. After the in vivo challenges of Streptococcus agalactiae and LPS, the mRNA expressions of OnC1qs were significantly up-regulated in liver. Meanwhile, the concentration variation of OnC1qs at the protein level from tilapia serum after challenge with S. agalactiae were measured by a competitive-inhibition ELISA. In addition, the up-regulation expressions of OnC1qs were also demonstrated in head kidney adherent leukocytes and the cell culture medium in vitro stimulation with S. agalactiae, Aeromonas hydrophila and LPS, respectively. Moreover, the recombinant OnC1qs enhanced expression of cytokines IL-6, IL-8 and IL-10 in head kidney adherent leukocytes, and were able to bind both heat-aggregated mouse IgG and IgM. Taken together, the results of this study indicated that OnC1qs might be involved in host defense against bacterial infection in Nile tilapia. Highlights: Full-length cDNA of three C1q subcomponents ( OnC1qA, OnC1qB and OnC1qC ) were identified and characterized in Nile tilapia. Expressions of OnC1qs were significantly up-regulated in liver upon LPS and bacterial challenges. Recombinant OnC1qs enhanced expressions of IL-6, IL-8 and IL-10 in adherent leukocytes in vitro. Recombinant OnC1qs possessed binding capability with heat-aggregated mouse IgG and IgM.